解题思路: 组合数学相加问题, 还没看懂公式怎么推导的。 先写上: f(n) = f(n-1) + (n-1)*f(n-2)
import java.util.Scanner; public class Main2 { public static final int M = 1000000007; public static void main(String[] args) { Scanner sc = new Scanner(System.in); long dp[] = new long[1000001]; dp[1] = 1; dp[2] = 2; dp[3] = 4; for (int i = 4; i < dp.length; i++) { dp[i] = (dp[i-1] + (i-1)*dp[i-2]%M) % M; } int T = sc.nextInt(); for (int cas = 1; cas <= T; cas++) { int n = sc.nextInt(); System.out.println("Case #"+cas+":"); System.out.println(dp[n]); } } }
原文地址:http://blog.csdn.net/first_sight/article/details/45999019